Crystal structure of N-(Ar)-N′-(Ar′)-formamidine, C14H12Br2N2O - Munzeiwa Wisdom A.; Zamisa Sizwe J.; Omondi Bernard (Zeitschrift für Kristallographie - New Crystal Structures)
C14H12Br2N2O, triclinic, P1‾$P\overline{1}$ (no. 2), a = 7.3470(3) Å, b = 9.4435(4) Å, c = 10.4335(4) Å, α = 78.943(2)°, β = 85.455(2)°, γ = 86.384(2)°, V = 707.37(5) Å3, Z = 2, Rgt(F) = 0.0313, wRref(F2) = 0.0927, T = 100 K.